Nonsurgical Management of Facial Masculinization and Feminization. (31st October 2018) - Ascha, Mona; Swanson, Marco A; Massie, Jonathan P; Evans, Morgan W; Chambers, Christopher; Ginsberg, Brian A; Gatherwright, James; Satterwhite, Thomas; Morrison, Shane D; Gougoutas, Alexander J
Abstract: Background: Transgender patients may seek nonsurgical methods for facial masculinization and feminization as an adjunct or alternative to undergoing surgical procedures. Objectives: The authors reviewed the existing literature regarding this topic and provided an overview of nonsurgical techniques for facial masculinization and feminization. Methods: A comprehensive literature search of the PubMed and MedLine databases was conducted for studies published through December 2017 for techniques and outcomes of nonsurgical facial masculinization and feminization. Keywords were used in performing the search. Data on techniques, outcomes, complications, and patient satisfaction were collected. Results: Four articles fit our inclusion criteria. Given the lack of published literature describing facial injectables in transgender patients, data from the literature describing techniques in cisgender patients were utilized to supplement our review. Conclusions: Facial feminization can be achieved through injectables such as neurotoxin and fillers for lateral brow elevation, lip augmentation, malar augmentation, and improvement of rhytids. Facial masculinization can be achieved with injectables used for genioplasty, jawline augmentation, and supraorbital ridge augmentation. One must develop best practices for these techniques in the transgender patient population and increase awareness regarding nonsurgical options. Level of Evidence: 4: